Evolution and Biogeography of Freshwater Snails of the Genus Bulinus (Gastropoda) in Afromontane Extreme Environments - Tumwebaze, I.; Clewing, C.; Chibwana, F. D.; Kipyegon, J. K.; Albrecht, C. (Frontiers in Environmental Science, 2022)
Mountains are considered island-like systems often characterized by exceptional biodiversity and endemism. There are many highly isolated mountain ranges in Africa that collectively have been called the Afromontane archipelago. Freshwater snails of the genus Bulinus are composed of many veterinary and biomedical important species. These intermediate hosts for schistosomiasis parasites are wide spread and some of the species are considered to be highly adapted to very harsh environmental conditions such as droughts or low temperatures. However, the extent to which the Bulinus have adapted to live in high-altitudes and factors influencing these range shifts are not well investigated. In this study, we analyzed pan-African Bulinus species from various habitats across different altitudinal ranges, focusing on the high mountains or ‘sky islands’ to examine how the contemporary climate and historical geological factors affect species distributions and evolutionary processes. Using a fossil-calibrated multigene phylogeny composed of two mitochondrial genes (cox1, 16S) and two nuclear genes (ITS2 and H3), we tested: a) how often and when extreme altitudes were colonized, b) what are the biogeographical affinities and degree of isolation of high-altitude species, c) which lineages diversified and evolved endemism in the Afromontane environments, and d) whether the Afromontane regions represent ‘sky islands’. Bayesian phylogenetic inference employing a fossil-calibrated molecular clock resulted in a strongly supported phylogeny resolving the relationships between the four Bulinus groups. High-altitude colonization exists exclusively within the Bulinus truncatus/tropicus complex. Several independent colonization events occurred in the Pliocene and Pleistocene throughout Africa, mostly from nearby regions of the respective mountain ranges. Most species evolved in low to mid-altitudinal ranges. Endemism is pronounced in the Ethiopian Highlands and those of Kenya and Lesotho. A previously unknown species was found at an extreme altitude (~4,000 m a.s.l.) on Mt. Elgon/Uganda extending the formerly known altitudinal maximum of the genus by roughly 900 m. The endemic species has already diverged in the Pliocene (~4 myr) and is currently characterized by low genetic diversity. There is further cryptic diversity in mountain ranges of Lesotho. Our findings are discussed in a biogeographical, conservation and biomedical context.